Analisis Pengaruh Pengeluaran Pemerintah Dan Kemiskinan Terhadap Pertumbuhan Ekonomi Di Sumatera Utara Tahun 1995 - 2014 - Nurul Izzah (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Government Expenditure and poor has a correlation with economic growth. High government expenditure and low poor will increase economic growth. The objective of the research was to analyze the influence of government expenditure and poor to economic growth of North Sumatera. The research was quantitative analytic with secondary data with the time series obtained from BPS (Central Bureau of Statistics) of North Sumatera. The result of the research showed that there was the positif influence of government expenditure variable to the variable economic growth. The result of the research also showed that there was the negative influence but not significant of poor variable to the variable economic growth.